RESEARCH TRENDS OF TECHNOLOGY INTEGRATION IN TEACHING ENGLISH GRAMMAR AS FOREIGN LANGUAGE: BIBLIOMETRIC ANALYSIS IN 2013-2023 - Erlinda, Rita; Agamas, Zetra Sivila (University of Kuningan, 2024)
Technological developments play an important role in education. To find out about these developments, it is necessary to conduct an analysis. One analysis that can be done to find out the development of technology is through bibliometric analysis. Bibliometric analysis is an analysis that explains the mapping process based on research trends that utilize analysis of metadata processing. Metadata is the main source for research results that researchers take from Scopus as a primary database. Researchers used quantitative and qualitative analysis methods. The purpose of this study is to analyze and determine the development trend of research related to the integration of technology in teaching grammar as a foreign language from 2013-2023. Data search and database analysis using Scopus software, Ms. Excel and supported by VOSviewer. The results of the research analysis show that in the last ten years from 2013-2023, the research trend on technology integration in teaching grammar as a foreign language is still relatively new and began to develop rapidly in 2022. The core topics that are still very new are in the time span between 2020-2022 which discuss multimedia systems, multimedia technology, educational computing. Meanwhile, the topic that is often discussed is multimedia technology which is then concluded to be the latest research map in the future.